Desenvolvimento de compósitos de matriz epóxi reforçada com fibras de vidro e nanopartículas de borracha para aplicação na área de blindagem - Garcia, André Zanchetta (Universidade Federal de São Carlos, 2013)
The use of shields in real estates (buildings and houses) in Brazil and in the World, the manufacture of armored doors, shields and walls is increasing and becoming a very promising market worldwide. Nowadays, in this shield area, the use of steel as raw material in the construction of panels for levels of protection called IIA is predominant. An alternative for this material is the development of composite materials of polymer matrix reinforced with fibers. In this context, the work involves the development of panels in composite of epoxy matrixes reinforced with fiberglass and elastomeric nanoparticles. The objective of this research was comparing the performance of composite panels with and without use of the particles. The method used for molding the composite panels was the lamination of sheets with six and ten HPG (High Performance Glass) layers of fiberglass by hot pressing process, using epoxy resin (DGEBA) with nanoparticles of rubber (butadiene) in addition as a matrix. To evaluate the performance of the molded composites, mechanical tests were realized, including Tensile Strength, Flexure Strength, Interlaminar Shear Strength, Izod Impact Strength, and Ballistic Impact tests (with 40 hand gun). Beyond that, other tests were also performed: physical-chemical, rate fiber/resin, void content and mass per unit area (weight). Besides that, some DMTA (Dynamic Mechanical Thermal Analyzer) were also performed in samples of resin (matrix) and laminates. Within the laminates molded and analyzed, it can be highlighted that the laminates containing elastomeric particles in the epoxy matrix, promoted the decreasing of density about 14% and increasing of the ballistic impact strength of the laminate.
Composites of epoxy matrix reinforced with fiberglass and nanoparticles of rubber for application in the shielding area
Keywords: materiais compósitos; compósitos poliméricos; nanopartículas; blindagem; compósitos; matriz epóxi; fibra de vidro; nanopartículas elastoméricas; shield; composite; epoxy; fiberglass; OUTROS